Determination of Potential Compounds of Stevia Leaves (Stevia rebaudiana Bertoni) Against DPP4 as Candidates for Antidiabetic Drugs - Resmi Mustarichie (Journal of Global Pharma Technology, 2020)
Diabetes mellitus is a metabolic disorder due to abnormalities in insulin secretion, insulin action, or both. Around 200 million people worldwide suffer from diabetes, most of which is type 2 diabetes. One of the targets of diabetes treatment is the DPP-4 enzyme which works to degrade incretin from the body. Sitagliptin, a DPP-4 inhibitor that has been approved for the treatment of type 2 diabetes. Besides using synthetic drugs, a biochemical compound can also be used for diabetes therapy, one of which is stevia leaf. This research was conducted to select compounds contained in stevia leaves based on their interaction with DPP4 in silico. The purpose of this study was to determine potential compounds from stevia leaves to be a candidate for antidiabetic drugs. Tests were carried out on DPP4 inhibitors, namely sitagliptin, and 10 compounds contained in stevia leaves. The results showed that there were three potential compounds namely isosteviol, steviol, and steviolmonoside. Testing the Lipinski's rule of five and pre-ADMET parameters implied that the three compounds had the potential to be used as candidates for antidiabetic drugs. Keywords: Stevia leaf, Stevia rebaudiana, Diabetes mellitus, DPP4, Molecular modeling.